2003
DOI: 10.1074/jbc.m207797200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Topology in C-terminal Region of the Human Plasma Membrane Anion Exchanger, AE1

Abstract: Human AE1 performs electroneutral exchange of Cl ؊ for HCO 3 ؊ across the erythrocyte membrane. We examined the topology of the AE1 C-terminal region using cysteine-scanning mutagenesis and sulfhydryl-specific chemistry. Eighty individual cysteine residues, introduced into an otherwise cysteine-less mutant between were inaccessible to the extracellular medium and thus localized to the intracellular surface of AE1. Functional assays revealed that one face of each of two AE1 TMs was sensitive to mutation. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
178
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(188 citation statements)
references
References 48 publications
4
178
0
6
Order By: Relevance
“…This glycine at position 609 is conserved among all known vertebrate AE1 gene family sequences, providing an idea of functional importance of this residue. Gly-609 is predicted to lie within the seventh transmembrane domain of the polytopic AE1 protein, toward its cytoplasmic end (29). Gly-609 is also located close to two residues where missense mutations have been reported, in codons Arg-589 and Ser-613, reinforcing the importance of this region of the multiple transmembrane-spanning half of the molecule.…”
Section: Discussionmentioning
confidence: 99%
“…This glycine at position 609 is conserved among all known vertebrate AE1 gene family sequences, providing an idea of functional importance of this residue. Gly-609 is predicted to lie within the seventh transmembrane domain of the polytopic AE1 protein, toward its cytoplasmic end (29). Gly-609 is also located close to two residues where missense mutations have been reported, in codons Arg-589 and Ser-613, reinforcing the importance of this region of the multiple transmembrane-spanning half of the molecule.…”
Section: Discussionmentioning
confidence: 99%
“…However, mutation of a CA2 binding site changed apparent transport stoichiometry (calculated from trans-monolayer short circuit currents) rather than abolishing HCO 3 Ϫ transport (21). Importance of the kAE1 C-terminal Tail to Plasmalemmal Anion Transport, and an Enlarged Functional Definition of the "Core CA2 Binding Site" of AE1-Recent cysteine accessibility scan evidence suggests that the human eAE1C-terminal cytoplasmic tail may extend from the terminal aa 911 as far as aa 872 (56). We previously reported that mouse eAE1 L890X (corresponding to human eAE1 L872X) exhibited loss-of-function in Xenopus oocytes, secondary to its intracellular retention (11).…”
Section: Interprotomeric Rescue Of Ae1-mediated Hcomentioning
confidence: 99%
“…Structure Figure 9 is a model of the topology of NBCe1-A, based on studies of the Cl-HCO 3 exchanger AE1 (86). All members of the family have a large cytoplasmic N terminus (Nt) and a much smaller cytoplasmic C terminus (Ct).…”
Section: Other Members Of the Slc4 Familymentioning
confidence: 99%